O segredo é a alma do negócio : mídias digitais móveis e a gestão da visibilidade do desejo homoerótico entre homens na região de São Carlos - Padilha, Felipe André (2015)
This dissertation wish to comprehend the strategic use of digital and mobile medias by men from countryside of São Paulo state that search for secret relations between men. My field has its base on Sao Carlos’s city, located in the central area of the state, and focus on the use of seeking applications for loving and sexual men partners between 18 and 60 ages. Considering Queer Theory, Brazilian studies of sexuality and other searches about digital medias, I take as hypothesis that the dynamic of secret that involves the homoerotic relations in this area has the objective to preserve the security in spaces such as family and work. Associating the ethnography work to the interviews, quantitative data and sources about use of digital medias, I look for understanding how the secret is connected to the interurban mobility, geographic location, life’s style, education, income and profession. Taking into consideration the social and technical context of medias reception, I analyze which displacements and repertory’s rearrangements to qualify the desire have been possible by means of the conventions and codes flow digitally mediated.